Co-morbidity pattern among type-II diabetes mellitus patients attending outpatient department of a rural tertiary care institute of North India - Pal, Ravinder; Verma, Ramesh Kumar; Singh, Navtej; Dr, Tarun (Asian Journal of Medical Sciences, 2021)
Background: Diabetes mellitus (DM) describes a group of metabolic disorders characterized by high blood glucose levels. People with diabetes have an increased risk of developing a number of serious life-threatening health problems resulting in higher medical care costs, reduced quality of life and increased mortality. Knowledge of the prevalence about coexisting medical conditions in specific population groups helps healthcare providers and policymakers to allocate health resources efficiently and tailor diabetic care management to effectively utilize healthcare programs while decreasing healthcare expenditure. Aims and Objectives: To find out the pattern of comorbidity burden among Type-II diabetes mellitus patients attending outpatient department of a rural tertiary care institute of North India. Materials and Methods: Study setting: Outpatient department (OPD) of General Medicine of Rural Tertiary Care Institute in North India. Study design: Descriptive, cross-sectional. Study population: Patients who had already been diagnosed by a physician of having Type 2 diabetes mellitus (T2DM) and attended OPD for follow-up during study period i.e. 1st November 2019 to 31st January 2020. Results: Among 82 study participants, 36 were males and 46 females. A total of sixty-six study participants had co-morbidities along with diabetes mellitus. Most common co-morbidity recorded was related to cardiovascular system and neuropathies. Adherence to treatment was followed by 46 (56%) and dietary advice by 42 (51%) study participants. Conclusion: In light of the chronicity of the disease and increasing prevalence of diabetes with associated comorbid conditions, there is a need for clearcut guidelines to address health risks of diabetes with other comorbid conditions. There should be provision for regular formal health education sessions to address co-morbidities, complications due to diabetes.